Agave negatively regulates YAP and TAZ transcriptionally and post-translationally in osteosarcoma cell lines. (1st October 2018) - Ferraiuolo, Maria; Pulito, Claudio; Finch-Edmondson, Megan; Korita, Etleva; Maidecchi, Anna; Donzelli, Sara; Muti, Paola; Serra, Massimo; Sudol, Marius; Strano, Sabrina; Blandino, Giovanni
Abstract: Osteosarcoma (OS) is the most aggressive type of primary solid tumor that develops in bone. Whilst conventional chemotherapy can improve survival rates, the outcome for patients with metastatic or recurrent OS remains poor, so novel treatment agents and strategies are required. Research into new anticancer therapies has paved the way for the utilisation of natural compounds as they are typically less expensive and less toxic compared to conventional chemotherapeutics. Previously published works indicate that Agave exhibits anticancer properties, however potential molecular mechanisms remain poorly understood. In the present study, we investigate the anticancer effects of Agave leaf extract in OS cells suggesting that Agave inhibits cell viability, colony formation, and cell migration, and can induce apoptosis in OS cell lines. Moreover, Agave sensitizes OS cells to cisplatin (CDDP) and radiation, to overcome chemo- and radio-resistance. We demonstrate that Agave extract induces a marked decrease of Yes Associated Protein (YAP) and Tafazzin (TAZ) mRNA and protein expression upon treatment. We propose an initial mechanism of action in which Agave induces YAP/TAZ protein degradation, followed by a secondary event whereby Agave inhibits YAP/TAZ transcription, effectively deregulating the Nuclear Factor kappa B (NF-κB) p65:p50 heterodimers responsible for transcriptional induction of YAP and TAZ. Highlights: Agave inhibits cell viability, colony formation, and cell migration, and induces apoptosis in OS. Agave sensitizes OS cells to cisplatin and radiation, to overcome chemo- and radio-resistances. Agave mechanism of action involves YAP/TAZ downregulation and NF-kB inactivation. YAP/TAZ exert oncogenic function in OS inducing proliferation, migration and chemoresistance. Saponins, contained within Agave, recapitulate Agave's mechanism of action.